Experimental investigation of naphthenic biofuel surrogate combustion in a compression ignition engine. (15th March 2022) - Ran, Zhongnan; Hadlich, Rodrigo Ristow; Yang, Ruinan; Dayton, David C.; Mante, Ofei D.; Assanis, Dimitris
Highlights: A naphthenic bio-blendstock was recovered using biomass catalytic fast pyrolis(CFP) CFP and hydrotreating processes were used to improve the quality of bio-blendstock. Naphthenic biofuel surrogate developed and tested in a compression ignition engine. 20% blend of surrogate fuel resulted in similar performance and emissions as diesel. High-quality naphthenic bio-fuel can be a sustainable alternative fuel for engines. Abstract: Biomass catalytic fast pyrolysis (CFP) integrated with hydrotreating (HT) produces advanced biofuels that could be used as bio-blendstocks to improve the properties of petroleum diesel fuels and enhance their combustion in compression ignition engines. The biofuels produced by CFP and HT are rich in naphthenes (cycloalkanes) that could improve cold-weather behavior and reduce the sooting propensity of blended diesel fuels. In this study, a surrogate fuel (SF1) that simulates a high-quality naphthenic bio-blendstock recovered from biomass CFP and HT was blended with research-grade No.2 diesel fuel (DF2) in different volume percentages and experimentally investigated in a single-cylinder Ricardo hydra diesel engine. Experiments were conducted by varying the fuel injection timings from the knock limit to the misfire limit at the same engine operating conditions for all of the SF1-DF2 blends (up to 40% by volume) and baseline No.2 diesel fuel. Engine output performance, combustion characteristics, and emissions including nitric oxides (NOx ), carbon monoxide (CO), total hydrocarbon (THC), and particulate matter (PM) were measured and analyzed. Experimental results showed that the surrogate blended at 10% and 20% by volume could yield comparable (<5%) engine output performance to that of baseline diesel at optimized fuel injection timings. Larger blend percentages (>20% & ≤40%) also exhibited good combustion controllability over a range of injection timings while sustaining a moderate reduction (∼10–20%) in engine output performance compared to baseline diesel. Increasing surrogate fuel blend percentage resulted in higher CO, THC, and PM emissions as cetane number decreased and the combustion ignition delay increased. This correspondingly reduced and retarded the onset and magnitude of the heat release, increased the burn duration and reduced the peak cylinder pressures and temperatures during combustion also causing lower NOx emissions for all SF1 blends. Results from the detailed experimental study ultimately indicate that based on the present surrogate fuel formulation representing a low-oxygenated naphthenic bio-blendstock produced from the CFP/HT pathway, such biofuels have the potential to be a viable drop-in fuel for compression ignition engines at moderate blend ratios without compromising engine performance and impacting exhaust emissions.